Perbedaan Kualitas Pelayanan Berdasarkan Waktu Tunggu Serta Rasio Rujukan Pasien Dokter keluarga - Wiji Astuti, Ida Srisurani; Murti, Bhisma; Probandari, Ari Natalia (STOMATOGNATIC- Jurnal Kedokteran Gigi, 2015)
Quality services doctor are represented by referral ratio and waiting time. In fact, the referral ratio in Jember shows higher than national value (15%). This study will analiyze the difference between payment system method, fee for service and capitation in family doctorâs quality services. This is an observasional study with cross sectional approach. Knowing the level of satisfaction, 214 patients who visited family doctor as both general and health insurance patients are testing by questionnare. In otherwise, 21 family doctors in Jember are represented referrals ratio by using referrals data. Using KolmogorofÂ  Smirnov and Man Whitney data analysis, the results showed a significant number.In addition, physicians with capitation payment method referred more patients by 3 times in average compared to physicians with fee for service payment method. This was seen from the p-value (0.002) < Î±(0,05). Similarly, waiting time variable with p-value (0,028) less than Î± (0,05). Capitation patients need more time Â± 3,77 minute thanfee for service.This mean there is significant different between capitation and fee for service patient in waiting time. Â  Keywords :payment method, waiting time, referral ratio